2005
DOI: 10.1029/2004jd005320
|View full text |Cite
|
Sign up to set email alerts
|

Estimates of ratios of anthropogenic halocarbon emissions from Japan based on aircraft monitoring over Sagami Bay, Japan

Abstract: Regional‐ and national‐scale emission rates of halocarbons have been a great concern in the field of global environmental studies and policy making. Emissions have been inventoried mainly by bottom‐up approaches, which involve adding up emissions from various industrial sources. To verify and supplement those bottom‐up inventories, top‐down approaches based on measurements of air concentrations are required. In this study, aircraft monitoring over Sagami Bay, Japan, was used to estimate the emission ratios of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
30
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 5 publications
(11 reference statements)
6
30
2
Order By: Relevance
“…We also present regional emissions estimates using interspecies correlation (ISC) methods (Yokouchi et al, 2005). Emissions of a number of trace gases from the Melbourne/Port Phillip region (CFCs, HCFCs, HFCs, carbon tetrachloride: Dunse et al, 2001Dunse et al, , 2002Dunse et al, , 2005Fraser et al, 2014a, b), including HFC-152a (Greally et al, 2007), have been estimated utilizing in situ high frequency measurements from Cape Grim and ISC with coincident carbon monoxide (CO) measurements.…”
Section: Regional Emissions Estimates Using the Inter-species Correlamentioning
confidence: 99%
“…We also present regional emissions estimates using interspecies correlation (ISC) methods (Yokouchi et al, 2005). Emissions of a number of trace gases from the Melbourne/Port Phillip region (CFCs, HCFCs, HFCs, carbon tetrachloride: Dunse et al, 2001Dunse et al, , 2002Dunse et al, , 2005Fraser et al, 2014a, b), including HFC-152a (Greally et al, 2007), have been estimated utilizing in situ high frequency measurements from Cape Grim and ISC with coincident carbon monoxide (CO) measurements.…”
Section: Regional Emissions Estimates Using the Inter-species Correlamentioning
confidence: 99%
“…Thus, there is presently large uncertainty in the emissions of HCFCs and HFCs from China. While for Japan, top-down estimates are also available (Yokouchi et al, 2005;Stohl et al, 2009), for the Taiwan region, South Korea and North Korea, there exists even less information than for China. This motivated the present study which uses measurement data from several stations in East Asia, an atmospheric transport model and an inversion algorithm to compute HCFC and HFC emissions for several countries in East Asia (mainland China including Hong Kong and Macao abbreviated as "China" in the following, North Korea, South Korea, Japan) as well as the Taiwan region.…”
Section: Introductionmentioning
confidence: 99%
“…Being a voluntary report system, PRTR may have a problem in the accuracy of data. Reports can be found that there are discrepancies between PRTR data and real release data [30][31][32]. The gap between PRTR and real data generally occurs in all chemicals rather than a specific chemical.…”
Section: Resultsmentioning
confidence: 99%